2014
DOI: 10.1007/s10661-014-3899-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution pattern of cyanobacteria community and its relationship with the environmental factors in Hongze Lake, China

Abstract: Hongze Lake, located in the east route of the South-to-North Water Diversion Project (SNWDP), is a potential drinking water source for the residents along this water diversion project. Based on a monthly sampling at 11 stations in three regions of Hongze Lake, the spatiotemporal distribution pattern of cyanobacteria community was comprehensively investigated from March 2011 to February 2013. A total of 23 cyanobacterial species which belong to 16 genera were identified, and Microcystis was the most predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Higher concentrations of As and Hg in both the sediment and overlying water were detected for the sites in the southwest part of Lake Hongze. This finding is consistent with those of previous investigations (Ma et al, 2013;Ren et al, 2014).…”
Section: Concentrations Of As and Hg In Sediment And Overlying Watersupporting
confidence: 94%
“…Higher concentrations of As and Hg in both the sediment and overlying water were detected for the sites in the southwest part of Lake Hongze. This finding is consistent with those of previous investigations (Ma et al, 2013;Ren et al, 2014).…”
Section: Concentrations Of As and Hg In Sediment And Overlying Watersupporting
confidence: 94%
“…The same occurrence was also discovered in other regulating lakes of the SNWDP, such as Hongze Lake [36], Nansi Lake [13], and Dongping Lake [37]. The first increase of cyanobacteria abundance occurred in May, followed by a decrease in June or July, and then it showed another increase in August.…”
Section: Seasonal Variation Of Cyanobacteria Species In Luoma Lakesupporting
confidence: 76%
“…These blooms are not only tolerant to higher insolation, but they also grow better at higher temperatures [29,30]. Therefore, Cyanobacterial blooms threaten George Lake in Uganda [29], as well as Taihu Lake [8] and Dianchi Lake [31] in China on a frequent basis.…”
Section: The Influence Of An Upstream Eutrophic Lake On Temporal and mentioning
confidence: 99%
“…Although WT is a crucial factor for temporal succession in phytoplankton [30,41], the correlation between WT and the abundance in the Tanglang River revealed that the river temperature did not significantly influence the growth or the loss of algae in the space. High temperatures (above 20 °C) favour the growth of Cyanobacteria [29].…”
Section: Impacts Of Environmental Variables On the Spatial Phytoplankmentioning
confidence: 99%